2017
DOI: 10.1080/10503307.2017.1393575
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for negative experiences during psychotherapy

Abstract: Patients require clear information, choice, involvement in decision-making, explicit contracting and clarity about sessions and progress. Opportunities for patient feedback should be the norm, where the therapist and service are vigilant for signs of deterioration and solutions considered. Clinical and methodological significance of this article: Estimates of "unwanted effects," including long-lasting effects, of psychotherapy have ranged from 3% to 15%. Few empirical studies have been conducted in this area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
2
40
0
4
Order By: Relevance
“…In contrast to pharmacological or even invasive techniques, VR appears comparatively harmless at first glance and likely free of serious side effects-akin to evaluations of the safety of psychotherapy where the discussion of possible side effects only very recently began. 86 A closer look reveals that the inherent potential of VR to modify behavior in a desired way at the same time holds the danger of bringing about undesired mental states that might influence the behavior of a person not only in virtuo but also in vivo. Despite these risks, clinical use of VR offers unique therapeutic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to pharmacological or even invasive techniques, VR appears comparatively harmless at first glance and likely free of serious side effects-akin to evaluations of the safety of psychotherapy where the discussion of possible side effects only very recently began. 86 A closer look reveals that the inherent potential of VR to modify behavior in a desired way at the same time holds the danger of bringing about undesired mental states that might influence the behavior of a person not only in virtuo but also in vivo. Despite these risks, clinical use of VR offers unique therapeutic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration in clinical samples involving children and young people has been shown to be around 7.7% for anxiety and 3.7% for depression (Edbrooke-Childs, Wolpert, Zamperoni, Napoleone, & Bear, 2018). Not all clinicians identified this as a type of harm which fits with the notion that additional factors need to be taken into account when making these judgements (Hardy et al, 2019;Linden, 2013). One reason for this is some patients do get worse before they get better (Kramer & Stiles, 2015), and clinicians may view this as part of the therapeutic process.…”
Section: Types Of Harmmentioning
confidence: 99%
“…Additionally, selecting the 'right' treatment, which was congruent with the patients' values and preferences, was also considered important. Previous research around negative experiences has highlighted that clinicians should understand patients' psychosocial context to get the right fit (Hardy et al, 2019). Yet, children The therapist being in a dominant position over the patient has been previously highlighted as leading to harm.…”
Section: Mechanisms Of Harmmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that psychological therapies can cause long‐term harm and that people who identify as LGBT and/or as black and minority ethnic are more likely to report harms . Hardy and colleagues found that a clear assessment, amongst other factors, fostered engagement and helped mitigate against potential long‐term harms …”
Section: Introductionmentioning
confidence: 99%